Release and Recharge of Fluoride Ions from Acrylic Resin Modified with Bioactive Glass - Raszewski, Zbigniew; Nowakowska, Danuta; Wieckiewicz, Wlodzimierz; Nowakowska-Toporowska, Agnieszka (Polymers, 2021)
BACKGROUND: Oral hygiene is essential for maintaining residual dentition of partial denture wearers. The dental material should positively affect the oral environment. Fluoride-releasing dental materials help to inhibit microbial colonization and formation of plaque as well as to initiate the remineralization process in the early cavity area. AIM: To evaluate fluoride ion release and recharge capacity, sorption, and solubility of polymethyl methacrylate (PMMA) dental resin modified with bioactive glass addition. MATERIALS AND METHODS: Two bioactive glass materials (5 wt% Kavitan, 10 wt% Kavitan, and 10 wt% Fritex) and pure 10 wt% NaF were added to dental acrylic resin. After polymerization of the modified resins, the release levels of fluoride anions were measured based on color complex formation by using a spectrophotometer after 7, 14, 28, and 35 days of storage in distilled water at 37 °C. Subsequently, specimens were brushed with a fluoride-containing tooth paste on each side for 30 s, and the fluoride recharge and release potential was investigated after 1, 7, and 14 days. Sorption and solubility after 7 days of storage in distilled water was also investigated. RESULTS: The acrylic resins with addition of 10% bioactive glass materials released fluoride ions for over 4 weeks (from 0.14 to 2.27 µg/cm2). The amount of fluoride ions released from the PMMA resin with addition of 10 wt% Fritex glass was higher than that from the resin with addition of 10 wt% Kavitan. The acrylic resin containing 10 wt% NaF released a high amount of ions over a period of 1 week (1.58 µg/cm2), but the amount of released ions decreased rapidly after 14 days of storage. For specimens containing 5 wt% Kavitan glass, the ion-releasing capacity also lasted only for 14 days. Fluoride ion rechargeable properties were observed for the PMMA resin modified with addition of 10 wt% Fritex glass. The ion release levels after recharge ranged from 0.32 to 0.48 µg/cm2. Sorption values ranged from 10.23 μm/mm3 for unmodified PMMA resin to 12.11 μm/mm3 for specimens modified with 10 wt% Kavitan glass. No significant differences were found regarding solubility levels after 7 days. CONCLUSIONS: The addition of 10 wt% Fritex and 10 wt% Kavitan bioactive glass materials to heat-cured acrylic resin may improve its material properties, with bioactive fluoride ion release ability lasting for over 4 weeks. The resin modified with 10 wt% Fritex glass could absorb fluoride ions from the toothpaste solution and then effectively release them. Addition of fluoride releasing fillers have a small effect on sorption and solubility increase of the modified PMMA resin. CLINICAL SIGNIFICANCE: The addition of bioactive glass may be promising in the development of the novel bioactive heat-cured denture base resin.
Keywords: PMMA; glass filler; bioactive acrylic resin; fluoride release; fluoride recharge